Vague de dénonciations : un groupe de soutien est créé dans le milieu littéraire - Larouche, Katy (Radio-Canada, 2020)
Keywords: Bibliographie; Nettoyer

Des violences sexuelles et des abus de pouvoir dénoncés dans le milieu littéraire - Bourel, Fanny (Radio-Canada, 2020)
Un groupe de 300 personnes s’est créé pour que les victimes témoignent et pour exprimer des revendications.
Keywords: Bibliographie; Nettoyer

La musique québécoise à l'ère de #MeToo - Caza, Pierre-Etienne (Actualités UQÀM, 2020)
La musicologue Vanessa Blais-Tremblay analyse l’évolution des chansons évoquant des violences à caractère sexuel.
Keywords: Bibliographie; Nettoyer

#metoo 2.0 to #meNOmore: Analysing Western Reporting About Sexual Violence in the Music Industry - Baker, Andrea; Williams, Katrina; Rodrigues, Usha M. (Journalism Practice, 2020)
In October 2017, #metoo 2.0 reinforces the gendered sexual violence in the creative sector [Marghitu, 2018. “It’s Just art: Auteur Apologism in the Post-Weinstein era”, Feminist Media Studies, 18(93): 491–494] Building on this movement, on 11 November that year, 2912 women “testified about the situation in the Swedish music industry”, signing an open letter condemning sexual violence [Nyheter, 2017. “2192 Women in the Swedish Music Industry Behind Appeal Against Sexism.” Dagens Nyheter, November 17. https://www.dn.se/kultur-noje/2192-women-in-the-swedish-music-industry-behind-appeal-against-sexism/]. After the Swedish initiative, on 12 December 2017, the #meNOmore hashtag was established by 1000 women who signed an open letter to the Australian music industry speaking out against similar behaviour [Whyte, 2017a. “Artists Speak Out Against Sexual Harassment in the Music Industry.” AM – ABC Radio, December 13. https://www.abc.net.au/radio/programs/am/sexual-harassment-in-the-music-industry/9253956]. Using a content analysis framework, this study examines the media framing of 26 stories about #meNOmore by the Western press from 22 November 2017 (height of the Swedish campaign) to 21 December 2017 (a week after the hashtag surfaced in Australia). Research from journalism studies and musicology highlights that sexual violence is historically engrained in the media and music industries. However, findings from our study of the first month’s coverage of the #meNOmore content analysis in 2017 reveal that media reports about women and sexual violence were framed around addressing gender inequality and systemic structural issues in the music industry. This raises the question, has the media has turned a corner when covering sexual violence in the post #metoo era?
Keywords: Bibliographie; Nettoyer

Raport de recherche de l'enquête pièces : violences sexuelles en milieu collégial au Québec - Bergeron, Manon; Gagnon, Audréanne; Blackburn, Marie-Ève; M-Lavoie, Dominique; Paré, Caroline; Roy, Sophie; Szabo, Andrea; Bourget, Claudie (Chaire de recherche sur les violences sexistes et sexuelles en milieu d’enseignement supérieur, Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Nettoyer

Dénoncer le harcèlement dans le milieu de l'improvisation - Radio-Canada (D'Est en Est, 2020)
Keywords: Bibliographie; Nettoyer

Entente collective entre l'Union des artistes et l'Association québécoise de la production médiatique (Artistes interprètes) (2020)
Keywords: Bibliographie; Nettoyer

Le jour où Éric Salvail est tombé - Bourgault-Côté, Guillaume (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Simple Plan renvoie son bassiste de tournée suite à des allégations d’inconduites sexuelles contre lui - Bibeault, Matt (99scenes, 2020)
C’est la firme de management de Simple Plan, Coalition Music, qui a confirmé la nouvelle. Chady Awad avait justement remplacé David Desrosiers lorsque ce dernier avait pris une pause de SP pour traiter sa dépression de 2017 à 2019. Awad était également photographe et vidéaste pour Simple Plan. Simple Plan a mis fin à sa... View Article
Keywords: Bibliographie; Nettoyer

De nouveaux gestes déplacés de musiciens dénoncés - Papineau, Philippe (2020)
Keywords: Bibliographie; Nettoyer

Politique de prévention du harcèlement psychologique ou sexuel au travail et traitement des plaintes - Théâtre de la Ligue Nationale d'Improvisation (2020)
Keywords: Bibliographie; Nettoyer

Milieu littéraire : le harcèlement touche une écrivaine sur trois - UNEQ (union des écrivaines et des écrivains québécois, 2020)
L’Union des écrivaines et des écrivains québécois (UNEQ) révèle les résultats d’une enquête menée auprès des autrices et auteurs québécois début octobre. Ces chiffres démontrent sans équivoque le déséquilibre du rapport de force entre les partenaires du milieu, déséquilibre qui mène bien souvent à des comportements inacceptables et à une omerta intolérable.
Keywords: Bibliographie; Nettoyer

Violences sexuelles et abus de pouvoir dans le milieu littéraire : il est plus que temps d’agir - UNEQ (Union des écrivaines et des écrivains québécois, 2020)
L’UNEQ donne son appui à la lettre rédigée par un groupe constitué de plusieurs centaines de femmes et minorités de genre déterminées à faire cesser une situation qui ne peut plus durer dans le milieu littéraire.
Keywords: Bibliographie; Nettoyer

Julien Lacroix visé par des allégations d’agressions et d’inconduites sexuelles - Pineda, Améli (Le Devoir, 2020)
Neuf femmes racontent avoir été victimes d'agressions ou d'inconduites sexuelles de la part de l'humoriste et comédien.
Keywords: Bibliographie; Nettoyer

Le milieu littéraire ébranlé par le mouvement de dénonciations - Lapointe, Josée (La Presse, 2020)
Le milieu littéraire fait face lui aussi au mouvement de dénonciations lancé il y a une dizaine de jours. Un groupe de 300 autrices et actrices de la chaîne du livre s’est formé de manière privée pour échanger à propos de cas d’inconduites sexuelles dont beaucoup ont été victimes.
Keywords: Bibliographie; Nettoyer

Violences sexuelles et abus de pouvoir dans le milieu littéraire: il est plus que temps d’agir - Déclaration commune (Liberté – Art et politique, 2020)
Déclaration commune
Keywords: Bibliographie; Nettoyer

Vague de dénonciations: des têtes tombent dans le milieu artistique - Bélanger, Cédric (Le Journal de Québec, 2020)
Les dénonciations font tomber Maripier Morin, Bernard Adamus et le patron de Dare To Care.
Keywords: Bibliographie; Nettoyer

Michel Brûlé reconnu coupable d’agression sexuelle - Béland, Gabriel (La Presse, 2020)
L’éditeur Michel Brûlé a été reconnu coupable mercredi d’agression sexuelle à l’endroit d’une auteure venue le rencontrer pour présenter un manuscrit.
Keywords: Bibliographie; Nettoyer

Best Practices for scenes involving nudity, intimacy, simulated sex and sexual violence - ACTRA (2020)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Je n'en ai jamais parlé à personne - Delvaux, Martine (Éditions Heliotrope, 2020)
«En octobre 2017, devant la vague de témoignages suscitée par le mouvement #moiaussi, j’ai senti une urgence : une fois sorties du silence, nous ne devions pas y retourner. C’est la raison pour laquelle j’ai lancé un appel. Ce livre est une chambre d’échos. Un chœur. Sans déesse ni héroïne en tête, des voix avancent. Nous faisons front commun.» Martine Delvaux «Je n'en ai jamais parlé à personne» : paroles recueillies et agencées par Martine Delvaux
Keywords: Bibliographie; Nettoyer

Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant) - Service correctionnel Canada (2020)
Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant)
Keywords: Bibliographie; Nettoyer

Webinaire contre le harcèlement et les violences (milieu cirque) pour artistes & travailleuses/eurs (2020)
En partenariat avec Juripop, En Piste vous présente le webinaire qui fût présenté dans le cadre de sa clinique contre le harcèlement et les violences dans le milieu cirque, qui a eu lieu le mardi 25 août 2020. Ce webinaire présente les services du Centre d'aide aux victimes d'actes criminels (CAVAC) et du Groupe d'aide et d'information sur le harcèlement sexuel au travail (GAIHST). Pour plus d'information et de ressources, visitez notre site web : www.enpiste.qc.ca
Keywords: Bibliographie; Nettoyer; À ajouter

Faire face au harcèlement en milieu de travail culturel: Un rapport sur les mécanismes de dénonciation et d’enquête existants et potentiels pour travailleurs et employeurs culturels - Labine, Lise; LeSage, Jeanne; Gagnon, Grégoire (Conseil des ressources humaines du secteur culturel, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer

Inconduite sexuelle: deux acteurs largués - Gendron-Martin, Raphaël (Le Journal de Montréal, 2020)
La valse des dénonciations pour inconduite sexuelle touchant le milieu culturel se poursuit.
Keywords: Bibliographie; Nettoyer

Safia Nolin accuse, Maripier Morin s’excuse - Groguhé, Marissa (La Presse, 2020)
L’auteure-compositrice-interprète Safia Nolin a provoqué une onde de choc en accusant mardi Maripier Morin de s’être livrée à du harcèlement sexuel, d’avoir commis une agression physique et d’avoir proféré des propos racistes lors d’une soirée dans un bar il y a deux ans. Des allégations en partie admises par l’animatrice télé, qui a présenté ses excuses le lendemain.
Keywords: Bibliographie; Nettoyer

Le milieu du jeu vidéo est-il indécrottablement discriminatoire? - Baillargeon, Stéphane (Le Devoir, 2020)
Le mouvement #MoiAussi frappe l’industrie de la manette et son sexisme systémique.
Keywords: Bibliographie; Nettoyer

La Cour d’appel donne raison à Gilbert Rozon - Corriveau, Jeanne (Le Devoir, 2020)
Le tribunal a annulé l’autorisation de l’action collective des Courageuses contre l’ancien magnat de l’humour.
Keywords: Bibliographie; Nettoyer

Quand se taire n’est plus une option - Papineau, Philippe; Renaud, Philippe (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Ubisoft : les démissions ne viendront pas à bout de la toxicité, disent des employés - Prévost, Hugo (Radio-Canada, 2020)
Le géant du jeu vidéo est plongé dans la tourmente depuis des semaines en raison d'allégations de harcèlement.
Keywords: Bibliographie; Nettoyer

Vague de dénonciations : au tour du cirque de faire son examen de conscience - Siag, Jean (La Presse, 2020)
Depuis quelques semaines déjà, les témoignages de violences sexuelles dans le monde du cirque se multiplient sur les réseaux sociaux. Au point où le regroupement national des arts du cirque, En Piste, a décidé de lancer dès mardi avec Juripop une clinique « contre le harcèlement et les violences dans le milieu du cirque ». La Presse a parlé aux instigateurs de Victims_Voices_Circus, espace virtuel où la parole de nombreuses artistes s’est fait entendre.
Keywords: Bibliographie; Nettoyer

Harcèlement à Ubisoft : la joueuse professionnelle Stéphanie Harvey témoigne - Agence France-Presse (Radio-Canada, 2020)
Une vague de dénonciations secoue Ubisoft et l'industrie du jeu vidéo depuis quelques semaines.
Keywords: Bibliographie; Nettoyer

Expériences de comportements sexualisés inappropriés, d’agressions sexuelles et de discrimination fondée sur le genre vécues par les travailleurs dans les provinces canadiennes, 2020 - Burczycka, Marta (Statistique Canada, 2020)
Keywords: Bibliographie; Nettoyer

A Single Drop of Water: Vulnerability, Invisibility, and Accountability in South Korean Theatre’s Moment of Crisis - Younghee, Park; Neideck, Jeremy (Performance Paradigm, 2020)
In early 2018, encouraged by the #MeToo movement sweeping the Western media landscape, Korean actor Park Younghee took to Facebook to write of her experiences of sexual harassment at the hands of a prominent theatre director and academic in the 1990s. While Younghee didn’t publicly name her abuser, it was not long before the social media machine identified Oh Tae Suk as the man she alluded to, and his world-renowned Geukdan Mokwha as the site of her abuse. Days later, prolific theatre director Kim Soo-hee made allegations of violence and sexual abuse against Lee Yoon-taek, the artistic director of the juggernaut theatre company Yeonhuidan Georipae, setting off a firestorm in the South Korean Media that has yet to die down. In South Korea, public performances of grief, allyship, and holding the government to account are hallmarks of democratic transformation. In this article, Park Younghee tells parts of her story to longtime collaborator Jeremy Neideck, and they attempt to weave a coherent narrative out of their yearlong discussion about the social, cultural, and political histories of Korea. This article seeks to illuminate, but not necessarily explain, the environments in which men like Lee Youn-taek and Oh Tae Suk were able to perpetrate abuse.
Keywords: Bibliographie; Nettoyer; Raphaël

A Nonbinary Actor Prepares (for Battle) - Woodzick, K. Bylines (Theatre Topics, 2020)
Keywords: Bibliographie; Nettoyer; Raphaël

Contemporary Feminist Protest in Ireland: #MeToo in Irish Theatre - Fitzpatrick, Lisa (Irish University Review, 2020)
This essay draws upon the work of Judith Butler, Sara Ahmed, and Germaine Greer to consider the #MeToo movement and its reflection in the work of the author's students and the scandal at Dublin's G...
Keywords: #MeToo; Bibliographie; Contemporary Feminism; Intergenerational; Intersectional; Nettoyer; Raphaël; Teaching

Le point de vue des improvisatrices au sujet des inégalités et des stéréotypes de genre véhiculés en improvisation théâtrale et ce que ceux-ci révèlent sur la société : Une recherche en travail social féministe - Robert Durant, Catherine (Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer; Sophie-Anne

Rapport de recherche sur l'état du milieu du spectacle d'improvisaiton théâtrale au Québec - Garneau, Jocelyn (Le théâtre de la Ligue Nationale d'Improvisation et la Rencontre Théâtre-Ados de Lavac avec l'appui financier du Ministère de la Culture et des Communications du Québec, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Patriarchal pits: the gendered experiences of female concert photographers - Lough, Kyser (Journal of Gender Studies, 2020)
While the presence of women in photojournalism is increasing, the way they are treated by their male counterparts remains unbalanced. Drawing from feminist theory and embodiment, this study examines how the gendered experience plays out for women in a particular niche of photojournalism; concert photography. The restricted access of the music scene and the embodied nature of photojournalism combine to present unique barriers for women. In-depth interviews with male and female concert photographers show women still face a form of patriarchal oppression in the field. This is seen through gendered language, such as ‘one of the guys’ versus a ‘mom in the pit’, embodied actions such as direct sexual harassment or indirect benevolent sexism, and in how women are questioned when they identify themselves as a photographer.
Keywords: Bibliographie; Myriam; Nettoyer; Photojournalism; concert photography; embodiment; feminist theory

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

#ThisIsArtSchool Is Exposing Allegations Of Racism & Sexual Abuse In Montreal Universities - Elliot, Teddy (MTL Blog, 2020)
As stories of racism and discrimination towards Black, Indigenous, and people of colour continue to dominate public discourse, more and more shocking allegations come to light about the lived experiences of systemic racism.
Keywords: Bibliographie; Nettoyer

Les expériences des victimes de violence sexuelle dans les programmes de justice réparatrice - Wemmers, Jo-Anne; Parent, Isabelle; Casoni, Dianne; Quirion, Marika Lachance (Centre international de criminologie comparée, 2020)
Keywords: Bibliographie; Expérience; Justice; Nettoyer; Système judiciaire; Victimes; Violence

Are Female Clowns Politically Incorrect? A Case Study on Female Clowns’ Political Engagement at the 7th “Esse Monte de Mulher Palhaça” festival in Rio de Janeiro - Cézard, Zed (Cadernos de Arte e Antropologia, 2020)
By linking the notion of politics with clown practices played out during the biennial festival «Esse Monte de Mulher Palhaça» in Rio de Janeiro (2018), dedicated specifically to female clowns, the relations between politics and feminism are raised, as well as the question of the place of clowns and women within the social system in which they act. In addition to reassessing the concept of politics through this new field of application, looking at what artistic practices convey or denounce as inequalities, allows us to identify politicized and political social elements. The private sphere, the power relations, the importance of gender, and the body and sexuality as treated in the festival’s performances raise political issues. We are lead to think of the phenomenon of Brazilian female clowns as a political space of claims, in particular feminist ones, and a resistance to dominant sexist normativity.
Keywords: Bibliographie; Brazil; Nettoyer; Sophie-Anne; female clowns; feminism; activism; politics

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Gender Equality in British Film-making: Research, Targets, Change - Cobb, Shelley; Williams, Linda Ruth (Women in the International Film Industry: Policy, Practice and Power, 2020)
In October 2017, the British Film Institute declared that it would commit to specific targets for gender equality and diversity in key production roles on films with support from the Film Fund. This decision by the BFI to set targets, arguably, did not come just from their own diversity and inclusion goals. Activist film-makers had previously called for targets for the Film Fund, especially for women directors. This chapter will give an accounting of the current state of gender (in)equality in the UK industry by: outlining new research that has clarified the stagnant inequality in the UK film industry; articulating the key role of a network of activist groups (that include researchers, professional and campaigning bodies, exhibitors and film-makers) to bring attention to the problem; putting pressure on the film industry and public bodies; and summarising institutional responses to that pressure since 2016, with a critical analysis of the potential and limits of the BFI’s relatively recently implemented diversity and equality targets.
Keywords: Bibliographie; Irina; Nettoyer

Sexual violence and nightlife: A systematic literature review - Quigg, Zara; Bigland, Charlotte; Hughes, Karen; Duch, Mariangels; Juan, Montse (Aggression and Violent Behavior, 2020)
Preventing and responding to sexual violence in nightlife settings is increasingly of global concern. The goal of this article was to identify and summarise academic studies on nightlife-related sexual violence. Specifically, to explore the nature, extent and consequences of, or associations with nightlife-related sexual violence, and interventions to prevent and respond. Of the 61 studies identified, 29 explored or reported on the nature of nightlife-related sexual violence, 22 provided information on extent, 38 on associations, and 19 on prevention and response. The majority of studies had been implemented in the past ten years (2009–2018) and in high-income countries. The review illustrates that nightlife-related sexual violence is pervasive, with lifetime prevalence reaching over 50% amongst numerous study samples. Studies suggest that a combination of factors at an individual, relationship, and community/environmental level is associated with nightlife-related sexual violence. No studies directly explored consequences, and few studies evaluated prevention and response approaches. Globally, further research is required to understand nightlife-related sexual violence, and inform the development of prevention programmes across all but particularly low and middle-income countries. Critically, interventions aimed at preventing and responding to nightlife-related sexual violence require thorough evaluation, with findings disseminated in both lay and academic literature.
Keywords: Bars; Bibliographie; Nettoyer; Nightlife; Prevention; Rape; Sexual; Violence

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Louis C.K.’s time’s up time out: rereading persona post-scandal - Piper, Melanie (Celebrity Studies, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Can You Come Back from Being Cancelled? A Case Study of Podcasting, Cancel Culture, and Comedians during #MeToo - Holman, Kylie J. (University of Nebraska, 2020)
Cancel culture is a new phenomenon of public shaming, facilitated by social media. This type of public shaming is accepted due to the alleged transgression of those who are cancelled. Social understanding of cancel culture does not generally allow for redemption. Using the theoretical framework of Feminist Media Studies (Van Zoonen, 1994) and Media Framing Theory (Gitlin, 1980), this study reveals the media’s role and power in the cancelling process. This study utilized a mixed-methods approach of case study and text analysis of episodes from the pop culture and politics podcast, Keep It. The case study focused on podcast episodes pertaining to two comedians cancelled for allegations of sexual misconduct in the #MeToo era [Oct. 2017 – Present]: Aziz Ansari and Louis C.K. The study also provided comparative cases of other comedians and comedic actors who were cancelled. Findings add to our understanding of cancel culture and appropriate methods of redemption for those who are cancelled.
Keywords: #MeToo; Bibliographie; Cancel culture; Comedians; Nettoyer; Podcasting; Redemption; Sophie-Anne

Comedy in the Era of #MeToo: Masking and Unmasking Sexual Misconduct in Stand-Up Comedy - Oppliger, Patrice; Mears, Kathryn (The Dark Side of Stand-Up Comedy, 2020)
With the announcement of allegations of sexual harassment and sexual assault against beloved comedians, we ask, “Can one separate the art from the artist?” Comedians are supposed to bring audiences joy and laughter; however, this role is challenged when there is incongruity between the comic persona and the real-life misdeeds of comedians. We explore the rise of the #MeToo movement and the role of comedy in exposing as well as masking allegations against Bill Cosby, Louis C.K., Al Franken, and Aziz Ansari. Guided by disposition theory and disengagement models, findings reveal factors of race, gender, and personal relationships appear to influence comedians’ assessment of fellow comedians accused of sexual misconduct. Audience members also appear to experience moral disengagement.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence